Clinical trials of artesunate plus sulfadoxine-pyrimethamine for Plasmodium falciparum malaria in Afghanistan: maintained efficacy a decade after introduction. (December 2016) - Awab, Ghulam; Imwong, Mallika; Pukrittayakamee, Sasithon; Alim, Fazel; Hanpithakpong, Warunee; Tarning, Joel; Dondorp, Arjen; Day, Nicholas; White, Nicholas; Woodrow, Charles
Abstract Background Combination therapy with artesunate plus sulfadoxine-pyrimethamine (SP) was adopted as recommended treatment forPlasmodium falciparum infection in Afghanistan in 2003. Methods A series of prospective clinical studies examining the efficacy of artesunate plus sulfadoxine-pyrimethamine (AS + SP) againstP. falciparum were undertaken in sentinel sites in Afghanistan from 2007 to 2014, accompanied by relevant molecular studies. The first study was a randomized trial of AS + SP versus dihydroartemisinin-piperaquine, while two subsequent studies were standard therapeutic efficacy studies of AS + SP. Results Three hundred and three patients were enrolled across four provinces in the north and east of the country. Curative efficacy was high in all the trials, with an adequate clinical and parasitological response (ACPR) of more than 95 % in all groups and trial stages. Genotyping for drug-resistance alleles atdhfr indicated fixation of the S108 N mutation and a prevalence of the C59R mutation of approximately 95 % across all sites. Other mutations indhfr anddhps remained rare or absent entirely, although five isolates from the first trial carried thedhps triple mutant SGEGA haplotype. In the last study undertaken in 2012–2014 the K13 artemisinin resistance marker was examined; only two of 60 successfully sequenced samples carried a K13-propeller mutation. Conclusions These data confirm maintained efficacy 10 years after introduction of artesunate plus SP as combination treatment ofP. falciparum in Afghanistan. The molecular data indicate that despite a substantial fall in incidence, resistance has not developed to artemisinins, or intensified to the ACT partner drug components. Trial Registration http://www.clinicaltrials.gov/ct NCT00682578, NCT01115439 and NCT01707199